Evolution of contourite systems in the late Cretaceous Chalk Sea along the Tornquist Zone. Issue 4 (13th March 2019) - Hübscher, Christian; Hseinat, Mu'ayyad Al; Schneider, Matthias; Betzler, Christian
Abstract: Based on integration of seismic reflection and well data analysis this study examines two major contourite systems that developed during the late Cretaceous in the southern Baltic Sea. The evolution of these Chalk Sea contourite systems between the Kattegat and the southern Baltic Sea started when Turonian to Campanian inversion tectonics overprinted the rather flat sea floor of the epeiric Chalk Sea. The Tornquist Zone and adjacent smaller blocks were uplifted and formed elongated obstacles that influenced the bottom currents. As a consequence of the inversion, the sea floor west of the Tornquist Zone tilted towards the north‐east, creating an asymmetrical sub‐basin with a steep marginal slope in the north‐east and a gentle dipping slope in the south‐west. A south‐east directed contour current emerged in the Coniacian or Santonian along the south‐western basin margin, creating contourite channels and drifts. The previously studied contourite system offshore Stevns Klint is part of this system. A second, deeper and north‐west directed counter‐flow emerged along and parallel to the Tornquist Zone in the later Campanian, but was strongest in the Maastrichtian. This bottom current moderated the evolution of a drift‐moat system adjacent to the elevated Tornquist Zone. The near surface Alnarp Valley in Scania represents the Danian palaeo‐moat that linked the Pomeranian Bay with the Kattegat. The previously studied contourite system in the Kattegat represents the north‐western prolongation of this system. This study links previous observations from the Kattegat and offshore Stevns Klint to the here inferred two currents, a more shallow, south‐east directed and a deeper, north‐west directed flow.